1995
DOI: 10.1073/pnas.92.12.5540
|View full text |Cite
|
Sign up to set email alerts
|

Priming of tumor-specific T cells in the draining lymph nodes after immunization with interleukin 2-secreting tumor cells: three consecutive stages may be required for successful tumor vaccination.

Abstract: Although both CD4+ and CD8+ T cells are clearly required to generate long-lasting anti-tumor immunity induced by s.c. vaccination with interleukin 2 (IL-2)-transfected, irradiated M-3 clone murine melanoma cells, some controversy continues about the site and mode of T-cell activation in this system. Macrophages, granulocytes, and natural killer cells infiltrate the vaccination site early after injection into either syngeneic euthymic DBA/2 mice or athymic nude mice and eliminate the inoculum within 48 hr. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…The success of allogeneic K1735-M2 vaccine cells is likely to be due to 'cross-priming' tumour antigen presentation whereby antigens on the tumour vaccine cells are released in the vicinity of the vaccination site and then processed and presented to naive T cells by autologous professional APC [5][6][7]25 making any requirement for MHC matching between the vaccine tumour cells and the vaccine recipient unnecessary. Although we do not know the possible cross-reactive antigen(s) being targeted by the immune response, the in vitro T cell work showed that the allogeneic vaccine generated B16-F10 specific CTLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of allogeneic K1735-M2 vaccine cells is likely to be due to 'cross-priming' tumour antigen presentation whereby antigens on the tumour vaccine cells are released in the vicinity of the vaccination site and then processed and presented to naive T cells by autologous professional APC [5][6][7]25 making any requirement for MHC matching between the vaccine tumour cells and the vaccine recipient unnecessary. Although we do not know the possible cross-reactive antigen(s) being targeted by the immune response, the in vitro T cell work showed that the allogeneic vaccine generated B16-F10 specific CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of both CD4+ve and CD8+ve T cells in mediating the effects of the allogeneic vaccine led us to believe that it operated via the indirect pathway of antigen presentation also known as 'cross-priming' 5,6 which involves the autologous APC. GM-CSF cytokine improves the recruitment and maturation of professional APCs 24 as well as the efficacy of autologous whole cell melanoma vaccines.…”
Section: Gm-csf Secreting Allogeneic Vaccine Is Effective In Treatmenmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from both bone marrow transplantation experiments (41) and histological investigations (32,42,43) in the murine system suggests the following working hypothesis for the events leading to the generation of cellular antitumor immunity. In the case of cellular cytokine-secreting irradiated vaccines, macrophage-like cells invade the vaccine deposit of irradiated cells and phagocytose the tumor cells within a relatively short period of days.…”
Section: Discussionmentioning
confidence: 99%
“…Various groups have shown that tumour cells transfected to express immunostimulatory cytokines are able to induce immune responses leading to rejection in experimental animal models (Fearon et al, 1990;Schmidt-Wolf and Schmidt Wolf, 1995;. In some cases, vaccination with cytokine-producing tumour cells protected against subsequent challenge with an otherwise lethal dose of wild-type tumour and eliminated pre-existing cancer deposits (Gansbacher et al, 1990;Dranoff et al, 1993;Maass et al, 1995;Zatloukal et al, 1995;Clary et al, 1997). Unfortunately, in man, the development of autologous tumour vaccines has proven to be more complex due to the requirement for establishing tumour cell lines for each patient and the need for efficient ex vivo transfection.…”
mentioning
confidence: 99%